2020
DOI: 10.3389/fbioe.2020.00552
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Bioactive Glass Composite Filaments for 3D Scaffold Manufacturing by Fused Deposition Modeling: Fabrication and Characterization

Abstract: Critical size bone defects are regularly treated by auto-and allograft transplantation. However, such treatments require to harvest bone from patient donor sites, with often limited tissue availability or risk of donor site morbidity. Not requiring bone donation, three-dimensionally (3D) printed implants and biomaterial-based tissue engineering (TE) strategies promise to be the next generation therapies for bone regeneration. We present here polylactic acid (PLA)-bioactive glass (BG) composite scaffolds manufa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 83 publications
5
89
0
Order By: Relevance
“…While pristine PLA scaffolds only showed certain cell alignment along printed threads, as reported by Grémare et al [64], the presence of HA induced matrix deposition at the pore edges and concavities (Fig. 9), which is in accordance with previous works [40,62]. AR staining and quantification of mineralization in our study indicated enhanced mineralization in the presence of HA, consistent with previous studies [26,38,65].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While pristine PLA scaffolds only showed certain cell alignment along printed threads, as reported by Grémare et al [64], the presence of HA induced matrix deposition at the pore edges and concavities (Fig. 9), which is in accordance with previous works [40,62]. AR staining and quantification of mineralization in our study indicated enhanced mineralization in the presence of HA, consistent with previous studies [26,38,65].…”
Section: Discussionsupporting
confidence: 93%
“…Similar studies using mineral reinforced 3D printed polymers consisting of PLA and bioglass have also reported a lack of significant improvement by the mineral incorporation in cell viability [62]. Babilotte et al reported a slightly increased adipocyte adhesion in the presence of 10% HA compared to pristine PLGA [26], although not statistically significant, similar to Orozco-Díaz et al describing slight improvements in the presence of 20% HA [38].…”
Section: Discussionmentioning
confidence: 67%
“…The pH of the solution increased during the incubation time, especially within the first day of soaking. The increase in pH values is related to the partial dissolution of the glass during the stages of the bioactivity process associated with the formation of a HAp layer on the surface of the 3D printed scaffolds, which in line with previous studies [46][47][48].…”
Section: Ph Measurementssupporting
confidence: 89%
“…Most importantly, though PLA has been proven to be processable through additive manufacturing techniques, it is certainly a more challenging material to process, because of its relevantly higher melting temperature compared to PCL and its likelihood to undergo thermal degradation phenomena for longer residence times within the extruder tank if ad hoc measures like the use of an inert gas feed are not undertaken. For this reason, most of the studies concerning fabrication of PLA/BG composites through melt-based additive manufacturing technologies rely on fused deposition Modeling approaches, requiring an intermediate step of filament fabrication [ 25 ]. The high thermal stability and processability of PCL, on the other hand, enables an easier fabrication of the composite scaffolds through PED, eliminating this intermediate step and thus potentially leading to a reduction in process complexity, fabrication times, and material waste.…”
Section: Introductionmentioning
confidence: 99%